Profil tingkat volume oksigen maskimal (vo2 maks) pada atlet sepakbola Universitas Pasir Pengaraian - Sinurat, Ridwan (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
This study aimed to determine the ability of maximum oxygen volume (VO2Max) of Pasir Pengaraian University football athlete. The method of this study was qualitative descriptive approach. The study form used was a test survey method with a multistage test or Muilti stage Fitness test (MFT). The data analysis used was percentage. The samples in this study were all football athletes of Pasir Pengaraian University. Based on the frequency data from VO2Max football athletes at Pasir Pengaraian University, it could be seen that the maximum oxygen volume (VO2Max) showed that none in the category was very less, less and very good. The very less criteria was 0%, the less criteria was 0%, the medium criteria was 16.6%, the good criteria was 83%, and the very good critria was 0%. Based on the results of the largest percentage analysis of VO2Max ability levels, the football team of the Pasir Pengaraian University mostly had good criteria.